Sex differences in associations between hair glucocorticoids and internalizing symptoms in adolescents - Yasmine Zerroug; Marie-France Marin; Mara Brendgen; Miriam Beauchamp; Jean R. Séguin; Sylvana M. Côté; Catherine M. Herba (Comprehensive Psychoneuroendocrinology)
From adolescence onwards, internalizing symptoms, such as depressive and anxiety symptoms, are twice as prevalent in adolescent girls than boys. Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, which controls production and regulation of glucocorticoids (cortisol and cortisone), is linked to depressive and anxiety symptoms. Findings on hair cortisol, cortisone and the cortisol/cortisone ratio in relation to these symptoms have been inconsistent, particularly in adolescent community samples. The ratio provides an indication of the active versus inactive balance of cortisol concentrations, as a proxy of 11-beta-hydroxysteroid dehydrogenase enzymes. In addition, few studies have investigated whether these associations are the same for adolescent girls and boys. Hair samples of 64 adolescent girls and 59 adolescent boys (aged between 14 and 15 years old) were analyzed using the liquid chromatography-mass spectrometry (LC-MS) extraction method. Internalizing symptoms were measured via validated self-reported online questionnaires. For adolescent boys, no associations between hair glucocorticoids and depressive or anxiety symptoms were found. For adolescent girls, the analyses revealed a positive association between hair cortisone concentrations and depressive symptoms. Our findings highlight significant sex differences in the mechanisms that might operate between glucocorticoid concentrations and internalizing symptoms. Future longitudinal studies could test the predictive, sex-dependent effect of hair glucocorticoids concentrations during adolescence on the development of internalizing disorders in adulthood. Gaining a deeper understanding of HPA axis functioning could help to identify youth who are at greater risk of developing stress-related psychopathologies.